PENETAPAN UPAH PEKERJA ANGKUT SAWIT DITINJAU DARI KOMPILASI HUKUM EKONOMI SYARIAH - Anita Widyawati; Loso Judijanto; Mohammad Anwar; Shohib Muslim (Yayasan Baitul Hikmah al-Zain, 2024)
Jorong rao-rao has a very large area of ​​land for planting plants so that many people in Jorong rao-rao rent land. Not a few people in Jorong rao-rao have an upper middle class economy and work in offices. So that it requires other people to harvest the plantation. There are two types of wages that are applied in Jorong rao-rao. The first is the amount of wages based on the proximity of the location of the oil palm plantations and the second the wages given are based on the amount of harvest. This research is a descriptive qualitative research. Data collection techniques used in this study were interviews and documentation. This research is used to see how the wages of oil palm workers in Jorong rao-rao are reviewed from the Compilation of Sharia Economic Law (KHES).